Nesbitt, Nick. The Price of Slavery: Capitalism and Revolution in the Caribbean. Charlottesville: University of Virginia Press, 2022. 274 pp. - Hoces-García, Alberto (Naveg@mérica, 2025)
Reseña del libro NESBITT, Nick. The Price of Slavery: Capitalism and Revolution in the Caribbean. Charlottesville: University of Virginia Press, 2022. 274 pp.